FINDINGS OF THE SPECIES AULACIDEA TRAGOPOGONIS (THOMSON) AND TIMASPIS CICHORII (KIEFFER) (HYMENOPTERA, CYNIPIDAE) IN SERBIA (Acta Entomologica Serbica, 2017)
In research on the fauna of insect parasitoids of cynipid gall wasps in Serbia, galls of the cynipid gall wasp species Aulacidea tragopogonis (Thomson, 1877) were found on Tragopogon dubius Scop. (Asteraceae), while galls of the species Timaspis cichorii (Kieffer, 1909) were found on Cichorium intybus L. (Asteraceae). As these are the only findings of the indicated cynipid gall wasps in Serbia to date, they are published in the present paper. Parasitoids obtained from the collected galls of these cynipid gall wasps are also published here.